The viability of convenience stores as perceived by Iloilo City residents - Aranas, Kathy S.; Cabasan, Noralyn E.; Cordova, Gissele Beatrice M.; Fuentes, Jenny L.; Guillen, Mitzi D.
Executive summary-In the past decade, the City of Iloilo has witnessed the apparent emergence of local convenience stores in the market. These stores marked an alternative way of shopping for the ilonggos. Most of these convenience stores were annexed to the gasoline station operations, some evolved from drug store chains, and some were autonomous store which basically offered food and grocery items. Because the primary existence of these stores lies n providing the Ilonggo residents with convenience, this study takes their view in the assessment of the viability of such stores in Iloilo City. The grocery buying behavior pattern and the demographic factors of Ilonggo residents, location and operational systems of convenience stores were taken into consideration to evaluate the relationship of such factors to the willingness of Ilonggos to purchase in convenience stores.